2021
DOI: 10.3389/fphar.2021.711788
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Supplementation for Rheumatoid Arthritis: A Promising Adjuvant Therapy in the Gut Microbiome Era

Abstract: Rheumatoid arthritis (RA) is a chronic immune-mediated inflammatory disease that ultimately leads to joint destruction and functional disability. Although the exact etiology of RA is not fully understood, it is well established that gut microbiota (GM) plays a vital role in the pathogenesis of RA, with accumulating evidence suggesting that gut dysbiosis induces a chronic inflammatory response that may be linked to disease development. Of interest, patients with RA have significant changes in the intestinal mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 130 publications
0
25
0
Order By: Relevance
“…Additionally, memory Th1 immune responses to Enterococcus hirae and Barnesiella intestinihominis was associated with prolonged progression-free survival in 38 advanced lung and ovarian cancer patients receiving chemotherapy ( Daillère et al., 2016 ). The gut microbiome has also been targeted for treatment of other autoimmune disorders, such as the use of Lactobacillus casei probiotic as an adjuvant therapy for rheumatoid arthritis ( Ferro et al., 2021 ). Therefore, the modulation of the gut microbiome or its metabolites (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, memory Th1 immune responses to Enterococcus hirae and Barnesiella intestinihominis was associated with prolonged progression-free survival in 38 advanced lung and ovarian cancer patients receiving chemotherapy ( Daillère et al., 2016 ). The gut microbiome has also been targeted for treatment of other autoimmune disorders, such as the use of Lactobacillus casei probiotic as an adjuvant therapy for rheumatoid arthritis ( Ferro et al., 2021 ). Therefore, the modulation of the gut microbiome or its metabolites (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Second, host‐targeted antirheumatic drugs, including methotrexate (5), azathioprine, and leflunomide (6), have off‐target effects on gut microbiota, raising the possibility that these drugs work by targeting both host cells and the microbiota to modulate inflammation. Third, therapies specifically targeting the gut microbiota, such as probiotics, have demonstrated success in alleviating autoimmunity, albeit in small patient populations (7). Finally, patients frequently report that dietary interventions alleviate disease, but whether this is due to shifts in the microbiota or direct effects on host immunity remains difficult to dissect in patients.…”
Section: Figurementioning
confidence: 99%
“…A body mass index (BMI) indicating adiposity is linked to the risk of RA development, and this is more significant in women [13]. Some studies have shown that the gut microbiome and its metabolites may induce RA by stimulating T H17 cells of mucosal immune tissue that control the production of autoantibodies [101][102][103][104].…”
Section: Pathogenesismentioning
confidence: 99%